2012
DOI: 10.14254/2071-789x.2012/5-1/1
|View full text |Cite
|
Sign up to set email alerts
|

Vocational Training and the Demands of Work: A Convention-Based Analysis

Abstract: Vocational training is a matter of considerable importance in developed countries. Attempts to evaluate the influence of this type of training on individuals' ability to enter the world of work have formed the basis of a number of largely empirical and quantitative studies in the economics of education and training. For all that, few analyses have sought to understand the decisions taken by economic agents, which are what is really at work behind the statistics. Thus the aim of the present article is to reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 23 publications
0
2
0
1
Order By: Relevance
“…The field has been described as fragmented due to the wide variety of areas taught, and correspondingly the diverse backgrounds and experiences of the teachers working within it (Grollmann, 2008;Köpsén, 2014;Tyler & Dymock, 2017). Due to teachers in the sector 'facing both ways' towards their pedagogic skill and occupational expertise, teachers are argued to draw on the values and experiences of their specific industry to inform their understanding of education (Bailly, 2012;Barnett, 2006;Colley, James, Diment, & Tedder, 2003). For example, the values, behaviours and ways of working of teachers in service industries and those teaching industrial trades have been demonstrated to contrast substantially (E. Smith & Teicher, 2017).…”
Section: Neoliberalism Within Educationmentioning
confidence: 99%
“…The field has been described as fragmented due to the wide variety of areas taught, and correspondingly the diverse backgrounds and experiences of the teachers working within it (Grollmann, 2008;Köpsén, 2014;Tyler & Dymock, 2017). Due to teachers in the sector 'facing both ways' towards their pedagogic skill and occupational expertise, teachers are argued to draw on the values and experiences of their specific industry to inform their understanding of education (Bailly, 2012;Barnett, 2006;Colley, James, Diment, & Tedder, 2003). For example, the values, behaviours and ways of working of teachers in service industries and those teaching industrial trades have been demonstrated to contrast substantially (E. Smith & Teicher, 2017).…”
Section: Neoliberalism Within Educationmentioning
confidence: 99%
“…Ihre empirischen Studien zeigen, wie eine unterschiedliche Qualität im Sinne von Spezifika von Kompetenzen über Lehr-Lernprozesse sowie die Formate der Evaluation des Gelernten sozial konstruiert werden. Frank Bailly und Elisabeth Chatel haben im Weiteren aufgezeigt, dass die Wertigkeit von Bildungstiteln nicht losgelöst und unabhängig von den Praxisfeldern bestimmt werden kann, in denen sie zum Einsatz kommen (Bailly 2012;Bailly und Chatel 2006, Chatel 2006. In Kritik an der Reproduktionstheorie von Bourdieu wird Bildung in diesen Zugängen nicht auf die Funktion eines Transmissionsriemens, der soziale Ungleichheit von einer Generation zur nächsten weiterreicht, reduziert.…”
Section: Qualität Und Bewertung Von Personenunclassified
“…Th e basic recruitment tools used in the internal recruitment include interviews with potential candidates, obtaining references from the candidate's direct superior, and using the results of competence measurement, provided that the organization has implemented human resources management system based on competence (Amstrong, 2011, Baran, Klos, 2014, Sirková, et al 2016. Th e advanced recruitment tools used in the internal recruitment include assessment centre (a multidimensional process of competency assessment conducted by a team of judges) which may be carried out either with the support of a third party or by a dedicated unit from inside the organization (Bailly, 2012). An organization which decides to recruit a new employee though the process of external recruitment has at its disposal two basic methods: passive recruitment and active recruitment.…”
Section: Literature Reviewmentioning
confidence: 99%